Fatty acid composition of sprat (Sprattus sprattus) and herring (Clupea harengus) in the Baltic Sea as potential prey for salmon (Salmo salar) - Keinanen, Marja; Kakela, Reijo; Ritvanen, Tiina; Myllyla, Timo; Ponni, Jukka; Vuorinen, Pekka J. (Helgoland Marine Research, 2017)
Sprat (Sprattus sprattus) and small herring (Clupea harengus) are the dominant prey fish of Atlantic salmon (Salmo salar) in the Baltic Sea. If the fatty acid (FA) proportions of sprat and herring differ, the dietary history of ascending salmon could be determined from their FA profiles. Therefore, we investigated the FA composition of several age groups of whole sprat and small herring, caught from the three main feeding areas of salmon in autumn and spring. Oleic acid (18: 1n-9) was the most prevalent FA in sprat and characteristic of this species. In herring, palmitic acid (16: 0) was the most common FA, but herring lipid was characterized by n-6 polyunsaturated FAs, and moreover, by palmitoleic acid (16: 1n-7) and vaccenic acid (18: 1n-7). Due to the higher lipid content of sprat, the concentrations of all other FAs, excluding these, were higher in sprat than in herring. The concentration of docosahexaenoic acid (DHA, 22: 6n-3) increased with an increase in the lipid content and was consequently highest in the youngest specimens, being in young sprat almost double that of young herring, and 2.6 times higher in the sprat biomass than in that of herring. As a result of a decrease in the DHA concentration with age, the ratio thiamine/DHA increased with respect to age in both species, and was lower in sprat than in herring. It is concluded that an abundance of DHA in the diet of salmon most likely increases oxidative stress because of the susceptibility of DHA to peroxidation, and thus decreases thiamine resources of fasting, prespawning salmon. Because the FA composition of sprat and herring differs, and the relative abundancies of prey fish differ between the feeding areas of salmon, the feeding area of ascending salmon can most probably be derived by comparing their FA profiles. Peer reviewed